Lessons Learned in the Development of Smallholder Private Irrigation for High-Value Crops in West Africa - Abric, Stephan; Sonou, Moise; Augeard, Benedicte; Onimus, Francois; Durlin, Dominique; Soumaila, Amadou; Gadelle, Francois (World Bank, Washington, DC, 2017)
The objective of this report is to identify and evaluate best practices in smallholder private irrigation in West Africa. The report is based on a comparative assessment of the smallholder private irrigation subsector in Burkina Faso, Mali, Niger, and Nigeria, which included a literature review, field visits, and workshops at both national and regional levels. The task lists for the assessment is provided in annex one. This report first presents the main features of smallholder irrigation and the development projects that have promoted its use in West Africa in chapter two. The authors then describe the low-cost technologies available for this type of irrigation, including drilling, pumping, and water distribution in chapter three. Chapter four reviews the successes and remaining challenges of the development projects involving smallholder private irrigation in West Africa. Chapter five draws the lessons learned from these experiences and proposes recommendations for future investments, including more support to the development of a supply-chain for low-cost irrigation technologies, the adoption of a programmatic approach, and the necessity for a comprehensive investment package including environmental impact mitigation to sustainably support smallholder irrigators.